The importance of past rifting in large igneous province development - R. Kounoudis; I. D. Bastow; C. J. Ebinger; S. Goes; P. Zhou; M. Musila; C. S. Ogden; A. Ayele (Nature, 2025)
Abstract Lithospheric thin zones, such as recently failed rifts, are generally assumed to be weak spots where magmatism and deformation can concentrate during rifting and large igneous province development 1–3 . Yet, the Turkana Depression in East Africa, the site of the failed 66-million-year-old Anza Rift, did not experience the widespread flood magmatism seen on the adjacent Ethiopian Plateau, despite being a lithospheric thin spot when the region encountered hot plume material around 45 million years ago 4 . Here we jointly invert surface-wave and receiver function data to constrain crustal and upper-mantle seismic structure below the Depression to evaluate lithospheric thermo-mechanical modification. Evidence for thick lower crustal intrusions, ubiquitous below the uplifted Ethiopian Plateau 5,6 , is comparatively lacking below the Depression’s failed Anza Rift system, which ongoing East African rifting is circumnavigating, not exploiting. The mantle lithosphere below the Depression has also retained its cool, fast-wavespeed ‘lid’ character, contrasting the Ethiopian Plateau. Volatile depletion during failed Anza rifting probably rendered the thinned lithosphere refractory without later rejuvenation. Subsequent rifting and magmatism thus initiated away from the still-thin Anza Rift, in regions where fertile lithosphere enabled melting and the sufficient lowering of plate yield strength. Areas of thinned lithosphere are thus not necessarily persistent weak zones where significant extension and magmatic provinces will develop.